Landau-Silin spin waves in conductors with impurity states - Ermolaev, Alexander; Ulyanov, Nikolay; Ермолаев, Александр Михайлович; Ульянов, Александр Михайлович (Saarbrücken : LAP LAMBERT Academic Publishing GmbH & Co. KG, Germany, 2012)
Theoretical investigation results of spin waves properties in nonmagnetic conductors and heterostructures with 2D electron gas in presence of impurity atoms be able to localize electrons are listed in monograph. The effect of quasi-local and magnetoimpurity states of electrons on dynamic spin susceptibility of electron gas, on spectrum and damping of spin waves are considered. New branches due to electron impurity states in spin wave spectrum are predicted. Methods of diagnostics of these waves in experiments with slow neutrons are proposed. Impurity atoms in a conductor exert a complicated influence on quasi-particle energy spectrum. They cause shift and spread of energy zones as well as state density rearrangement accompanied by appearance of both local and quasi-local levels. A local state concept in non-ideal crystalline lattice oscillation spectrum has been suggested by I. M. Lifshits [in 1940s. These investigations were continued in the Kagan and Iosilevskii and Brout and Visscher articles in which impurity atom quasi-local oscillations in lattice was predicted. A theory of other quasi-particles electrons and magnons was been elaborated at the same time.
Спиновые волны Ландау-Силина в проводниках с примесными состояниями
Keywords: NATURAL SCIENCES::Physics; примесные состояния электронов в твердых телах; коллективные возбуждения; Landau-Silin spin waves; spin waves in a Fermi-liquid of nonferromagnetic metals; quasi-local (resonance) and magnetoimpurity states of electrons; dynamic spin susceptibility of electrons; neutron magnetic scattering in non-ferromagnetic metals; Silin spin waves in two-dimensional electron gas; spin waves in a fermi-liquid of non-ferromagnetic metals; tensor of dynamic spin susceptibility of metals; quasilocal states of electrons in a magnetic field; spin waves in non-ferromagnetic metals; neutron magnetic scattering in non-ferromagnetic metals